PEMUNGUTAN RETRIBUSI PERPANJANGAN IZIN TENAGA KERJA ASING DI KOTA BATAM TAHUN 2019 – 2020 - Salsabila, Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Foreign Worker Employment Permit, abbreviated as IMTA, is a written permit to employ foreign workers granted by an appointed official to the employer of foreign workers. Furthermore, compensation is a fund that must be paid by the employer of Foreign Workers to the State/Region for the use of foreign workers. The Extension of Foreign Worker Employment Permit (IMTA) Levy has a significant role for the Batam City area, including as a source of regional cash flow, as a limitation of movement for Foreign Workers (TKA) working in Batam City and as one of the ways taken by the local government in the framework of technology transfer through cooperation between local workers and foreign workers. In addition, the levy funds are also used to finance training for workers including graphic design, autocade, sewing, and welder training and are used as a source of funding to take care of the foreign worker permits themselves. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then the location of the research is in Batam City, Riau Islands. This study that in its implementation the collection of levies on the extension of foreign worker permits in Batam City in 2019-2020 has been running well although not yet fully optimal. The indicator of the cause of the obstruction of the implementation of the foreign worker extension levy itself is the failure to achieve data and targets. This is one of the causes of the suboptimal implementation of the levy and the results of achieving the target of the levy itself. In its implementation there are also internal problems such as errors in payment which cause disputes with companies that finally submit a refund (DPKK) which takes quite a long time, The conclusion in the implementation of the foreign worker extension levy in Batam City 2019- 2020 is said to be successful but has not run optimally. This can be seen from several causes of obstacles that occurred during the implementation of the collection. Keywords: IMTA, Retribution, Foreign Workers.